Enhancing student participation in learning to write a recount text: Learning from EFL pre-service teachers in implementing R2L pedagogy - Iyen Nurlaelawati; Wawan Gunawan; Nenden Sri Lengkanawati (Indonesian Journal of Applied Linguistics, 2022)
Reading to Learn (R2L) Pedagogy evolved from the development of genre pedagogy, which has gained more attraction in language teaching and learning. In an effort to continuously yield empirical advantages in supporting students’ learning in reading and writing, genre pedagogy has been much researched in the field of teaching involving experienced teachers. Nonetheless, investigating R2L pedagogy enacted by EFL preservice teachers having no experience in teaching leaves a gap in the existing literature, thus becoming the aim of this study. The study was carried out in a case study design, involving three preservice teachers in a teaching practicum program as the participants. The study took place in a high school in West Java Province, Indonesia. The data were collected through classroom observations and interviews, which then were analyzed to search for themes generated by a qualitative approach and amplified by pedagogic register analysis.  The findings showed that through adaptation and modification, the participants implemented most of the stages of R2L pedagogy in their teaching context. The phases of teaching and learning created classroom interaction better between the preservice teachers and students, leading to enhancing student participation in the teaching and learning activities. The analysis also indicated the challenges that the participants encountered, such as text selection and contextual strategies of detailed reading. This study suggests that R2L pedagogy provides purposeful staged activities significant in enhancing students’ participation, thus leading to better student learning engagement.